Cyanobacteria and Microalgae: A Renewable Source of Bioactive Compounds and Other Chemicals. (June 2015) - Encarnação, Telma; Pais, Alberto A.C.C.; Campos, Maria G.; Burrows, Hugh D.
Microalgae and cyanobacteria are rich sources of many valuable compounds, including important bioactive and biotechnologically relevant chemicals. Their enormous biodiversity, and the consequent variability in the respective biochemical composition, make microalgae cultivations a promising resource for many novel chemically and biologically active molecules and compounds of high commercial value such as lipids and dyes. The nature of the chemicals produced can be manipulated by changing the cultivation media and conditions. Algae are extremely versatile because they can be adapted to a variety of cell culture conditions. They do not require arable land, can be cultivated on saline water and wastewaters, and require much less water than plants. They possess an extremely high growth rate making these microorganisms very attractive for use in biofuel production – some species of algae can achieve around 100 times more oil than oil seeds. In addition, microalgae and cyanobacteria can accumulate various biotoxins and can contribute to mitigate greenhouse gases since they produce biomass through carbon dioxide fixation. In this review, we provide an overview of the application of microalgae in the production of bioactive and other chemicals.